Involvement of autologous myeloid dendritic cells in the evaluation of immediate hypersensitivity reactions to betalactams - Fernández-Santamaría, Rubén; Ariza, Adriana; Bogas, Gador; Salas, Maria; Calvo-Serrano, Silvia; Frecha, Cecilia; Mayorga Mayorga, Cristobalina; Torres-Jaén, María Josefa; Fernández-Duarte, Tahía Diana (Elsevier, 2024)
Background: Amoxicillin (AX) and clavulanic acid (CLV) are the betalactam antibiotics (BLs) most used to treat bacterial infections, although they can trigger immediate hypersensitivity reactions (IDHRs). The maturation analysis of monocyte-derived dendritic cells (moDCs) and their capacity to induce proliferative response of lymphocytes are useful to test the sensitisation to a drug, although without optimal sensitivity. Nevertheless, this can be improved using directly isolated DCs such as myeloid DCs (mDCs). Methods: mDCs and moDCs were obtained from 28 allergic patients (AP), 14 to AX, 14 to CLV and from 10 healthy controls (HC). The expression of CCR7, CD40, CD80, CD83, and CD86 was analysed after stimulation with both BLs. We measured the capacity of these pre-primed DCs to induce drug-specific activation of different lymphocyte subpopulations, CD3+, CD4+, CD8+, CD4+Th1, and CD4+Th2, by flow cytometry. Results: Higher expression of CCR7, CD40, CD80, CD83, and CD86 was observed on mDCs compared to moDCs from AP after stimulating with the culprit BL. Similarly, mDCs induced higher proliferative response, mainly of CD4+Th2 cells, compared to moDCs, reaching up to 67% of positive results with AX, whereas of only 25% with CLV. Conclusions: mDCs from selective AP efficiently recognise the culprit drug which trigger the IDHR. mDCs also trigger proliferation of lymphocytes, mainly those with a Th2 cytokine pattern, although these responses depend on the nature of the drug, mimicking the patient's reaction.
RFS, AA, GB equally contributed to this work. CM, MJT and TDF equally contributed to this work.
https://openpolicyfinder.jisc.ac.uk/id/publication/11277
Keywords: Antibióticos betalactámicos - Efectos secundarios; Células dendríticas; Alergia a los medicamentos; Dendritic cells; Immediate drug hypersensitivity reactions; Lymphocyte transformation test; Maturation; Proliferation